2015
DOI: 10.1007/s12062-015-9131-1
|View full text |Cite
|
Sign up to set email alerts
|

Working Pensioners in Germany and the UK: Quantitative and Qualitative Evidence on Gender, Marital Status, and the Reasons for Working

Abstract: Taking paid work among men and women beyond pension age as an example, the contribution examines the interrelationship between life courses, gendered welfare regimes, and later-life employment outcomes. Using both quantitative and qualitative data, the article focuses on the role of inequalities, gender and marital status for working despite receiving a pension, and on the subjective reasons for this employment. The quantitative analyses are based on the English Longitudinal Study of Ageing (ELSA) and the Germ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
1
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 22 publications
3
23
1
3
Order By: Relevance
“…They have different reasons for working in retirement and different preferences regarding their future working conditions. The first finding is reflected in qualitative research from Germany that also found a great variation in the reasons for working beyond retirement (Hokema and Scherger 2016). Relating the results back to the three theories-continuity theory, work-role-attachment theory and the cumulative disadvantage theory-one comes to the conclusion that the 'classical' continuity theory (Atchley 1989) seems to apply mainly to self-employed in predicting older workers' wishes regarding post-retirement work but not to others as these have been shown to be very heterogeneous.…”
Section: Discussionmentioning
confidence: 98%
“…They have different reasons for working in retirement and different preferences regarding their future working conditions. The first finding is reflected in qualitative research from Germany that also found a great variation in the reasons for working beyond retirement (Hokema and Scherger 2016). Relating the results back to the three theories-continuity theory, work-role-attachment theory and the cumulative disadvantage theory-one comes to the conclusion that the 'classical' continuity theory (Atchley 1989) seems to apply mainly to self-employed in predicting older workers' wishes regarding post-retirement work but not to others as these have been shown to be very heterogeneous.…”
Section: Discussionmentioning
confidence: 98%
“…Using data from the DEAS and the English Longitudinal Study of Ageing (ELSA), it was shown that fewer people are forced to pursue post-retirement employment in Germany than in England, mainly for institutional and/or structural reasons. 22 , 23 Besides the occupational, financial and health factors that affect post-retirement employment, 24 psychological experiences of ageing also influence the decision to continue working after retirement. 25 …”
Section: What Has It Found? Key Findings and Publicationsmentioning
confidence: 99%
“…Die Lebensphase des Ruhestands ist ein bedeutender Bestandteil des institutionalisierten Lebenslaufs in westlichen Gesellschaften (Kohli 1985), der von wohlfahrtsstaatlichen Institutionen, aber auch vom Erwerbs-und vom Bildungssystem geprägt wurde. Das definierende Merkmal dieser Lebensphase, welches auch die auf sie gerichteten normativen Erwartungen bestimmt, ist die Kombination von Nicht-Erwerbstätigkeit und Rentenzahlungen.…”
Section: Erwerbstätigkeit Jenseits Der Rentengrenze -Einordung Und Reunclassified
“…Die (Wieder-)Aufnahme einer Erwerbstätigkeit oder das Weiterarbeiten im Alter sind Beispiele biographischen Handelns im Kontext der den Lebenslauf formenden Institutionen des Rentensystems und des Arbeitsmarkts. Diese stellen moderne "sekundäre Institutionen" dar (Leisering 1998), die im Zuge von Individualisierungsprozessen (Beck 1986;Kohli 1985) primäre Institutionen wie die traditionelle Familie oder Dorfgemeinschaften zunehmend ablösen. Während primäre Institutionen direkte Handlungsregeln vorgeben, machen sekundäre Institutionen keine Handlungsvorgaben, sondern schaffen nur Handlungsvoraussetzungen oder -rahmen und damit Handlungsspielräume (Weymann 1989).…”
Section: Der Institutionalisierte Lebenslauf: Biographisches Handeln unclassified
See 1 more Smart Citation